Temporal Development Patterns of Inner Solar System Colonization in Comparativist Perspective - Ehret , Marian; Havarangsi, Phanrajit (Journal of Politics and Governance, 2025)
This qualitative study asked research questions on Moon and Mars colonization, as these celestial bodies in the inner solar system attract human presence. In which timeframes will the colonization of Moon and Mars begin and result in creating habitats as political entities with human populations? Which media content provides educational examples for Moon and Mars colonization, depicting nature and timeframes of the colonization processes realistically? The objectives were to determine timeframes for Moon and Mars colonization and to identify educational media examples for both processes. Literature on political and media-reflected space colonization highlighted the need to identify precise temporal colonization patterns and media content, which informed these timeframes. Within the Historical Cycles theory, philosopher Oswald Spengler’s analogy approach was employed as a research method, using political-historical comparisons between the Roman conquests of Gaul and Britain and the Western colonization timeframes of Moon and Mars, projecting past Roman events onto future Western occurences. Outcomes revealed that limited exploratory base creation on the Moon would begin after the human return in 2025. These bases would evolve into specialized exploratory bases around 2045, with human settlements forming as political entities in the 2090s, reaching growth saturation in the 2120s. Exploratory Martian bases would emerge from the 2090s onward, with human settlements forming political systems from the 2160s or 2190s onward, reaching development consolidation in the 2230s. Media content that communicated timeframes of lunar and Martian colonization realistically included the movies Moon (2009), Ad Astra (2019), and the TV show The Expanse (2015–2022).